Facteurs déterminants la comptabilisation des actifs immatériels par les dirigeants des entreprises de l'espace OHADA : cas du Togo - Koumagnanou, Komivi (2018)
The OHADA accounting framework is not immune from the choice of accounting policies for intangible assets. The need to make an accounting choice for intangible assets depends on a number of factors. This article aims to identify the motivations of managers in the choice of accounting for intangible assets. In a second step, we described the methodological approach of our work. Thus, we proceeded to the empirical study which is both qualitative and quantitative. The collected data was then analyzed. From the companies' case, it was found that the tax reasons, the accounting principles, the logic of obtaining the loans, the follow-up of the practice of the competitors, the implementation of the recommendations of audit, the sense of limiting the wage demands are pushing executives to make accounting choices for intangible assets.
Keywords: Accounting choice; Actif immatériel; Choix de comptabilisation; Intangible assets; OHADA